1992
DOI: 10.1016/s0886-3350(13)80105-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a superficial and a deep scleral pocket incision on the incidence of hyphema

Abstract: Deep tunnel scleral pocket incisions were developed to control surgically induced astigmatism following cataract and intraocular lens implantation surgery. A more superficial, shallow scleral pocket incision was developed to reduce the rate of postoperative hyphema. To test its effectiveness, a randomized prospective clinical study was performed. One hundred twenty-nine eyes of 129 patients were randomized: 66 to receive a deep tunnel pocket and 63 to receive the superficial pocket. In both groups the incision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Lorsque la pré-incision est profonde, le tunnel est profond et il y a risque de traumatisme de l'iris et par conséquent un risque plus élevé de survenu d'hyphéma. John et al ont rapporté 34% de cas d'hyphéma lorsque les tunnels étaient profonds contre 6% lorsqu'ils étaient superficiels [ 20 ]. Aucun cas d'endophtalmie n'a été noté dans notre série.…”
Section: Discussionunclassified
“…Lorsque la pré-incision est profonde, le tunnel est profond et il y a risque de traumatisme de l'iris et par conséquent un risque plus élevé de survenu d'hyphéma. John et al ont rapporté 34% de cas d'hyphéma lorsque les tunnels étaient profonds contre 6% lorsqu'ils étaient superficiels [ 20 ]. Aucun cas d'endophtalmie n'a été noté dans notre série.…”
Section: Discussionunclassified
“…A tear may happen during any steps of cataract surgery. Literature has identified that technique of wound creation and instruments manipulation in and out of the eye as among the commonest steps responsible for the initial tear (John et al 1992;Zusman et al 1987;Zeiter et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cataract surgery, it has been reported to occur after iridectomy, 5 trabeculectomy, 12 viscocanalostomy, 13 penetrating keratoplasty, 14 lamellar keratoplasty, 15 pars plana vitrectomy, 16 and during insertion of foldable and nonfoldable IOL. [17][18][19] Occurrence of DMD after phacoemulsification has been attributed to various factors including shallow anterior chamber, 20 accidental insertion of the instruments between the stroma and the DM, use of blunt microkeratomes, 21 shelved incisions, 22 anteriorly placed incisions, 23 or inadvertent injection of saline, 3 viscoelastic, 19,22,24 or prophylactic antibiotics into the space between the deep stroma and the DM. 25 As compared with manual extracapsular cataract extraction, phacoemulsification requires repeated manipulations at the edge of the incision, secondary to introducing the instrument in and out of the anterior chamber.…”
Section: Discussionmentioning
confidence: 99%